Metaphysics of States of Affairs Truthmaking, Universals, and a Farewell to Bradley's Regress - Meinertsen, Bo R. (Philosophical Studies Series,, 2018)
This book addresses the metaphysics of Armstrongian states of affairs, i.e. instantiations of naturalist universals by particulars. The author argues that states of affairs are the best candidate for truthmakers and, in the spirit of logical atomism, that we need no molecular truthmakers for positive truths. In the book's context, this has the pleasing result that there are no molecular states of affairs. Following this account of truthmaking, the author first shows that the particulars in (first-order) states of affairs are bare particulars. He then argues that the properties in states of affairs are simple, non-relational and concrete universals. Next, he argues that (material) relations in states of affairs are external relations. Lastly, he argues that a state of affairs is unified by a distinctive formal relation without giving rise to Bradley's regress. Written in a relatively non-technical style, the book offers a valuable resource for philosophers working on analytic metaphysics and ontology, as well as their graduate students.